Paradigmatic Reverse in the Legal Policy of the Notion of Deliberative Democracy from Peoples Consultative Assembly (Majelis Permusyawaratan Rakyat) to Village (A Preliminary Study) - Junaenah, Inna (Faculty of Law, Padjadjaran University, 2015)
AbstractThis article aims to assert that some regulatory mechanisms, such as the appointment of members of and the voting for decision in both Indonesia Peoples Deliberative Assembly (MPR) and village flows in a formalizing pattern from the top governmental body of the central, to the regional, and to the ends at the boom level, the village. This also applies the procedural aspects of the democratic system where the organizational body is made as formal, uniform, and permanent in structure (despite the periods). This somehow seems contradictory with the noon of deliberative democracy (demorasi permusyawaratan) once upheld by the founding fathers of Indonesia. However, the vague understanding surrounding the noon of deliberative democracy necessitates a closer study for a more comprehensive overview, which should also be conducted for beer comprehension on the concept of democracy adopted by the MPR. This article serves only as a preliminary study to prelude a more in-depth study. The derivation of legal policy in this article has the purpose of identifying the political direction towards which the village democracy was taken. This article highlights a paradigmatic shift in the legal policy change of the democratic pattern from the village to the MPR, then later from the MPR to the village.Arus Balik Polik Hukum Gagasan Demokrasi Permusyawaratan dari Majelis Permusyawaratan Rakyat ke Pemerintahan Desa (Suatu Kajian Awal)AbstrakPada tulisan ini hendak dikemukakan pengaturan, misalnya mengenai pengambilan keanggotaan dan putusan, serta kelembagaan desa, menamakan pola imitasi dari kelembagaan di pusat, daerah, maupun desa begitu pula mengenai tata cara kehiduan berdemokrasi dari kelembagaan demokrasi, badan representasinya dibuat secara formal, seragam, dan permanen walaupun terdapat periodisasi. Hal ini tampak kontradif dengan konsep demorasi permusyawaratan yang diusung oleh para founding fathers ketika Indonesia berdiri. Namun demikian, pemahaman mengenai demokrasi permusyawaratan itu sendiri masih harus digali agar lebih tergambar secara komrehensif begitu pula mengenai konsep berdemokrasi dalam kelembagaan. Tulisan ini merupakan kajian awal sebagai pengantar untuk kajian yang lebih mendalam. Alasan hal ini ditarik sebagai sebuah politik hukum adalah untuk melihat apabila terdapat desain arah kebijakan terhadap entitas desa untuk dapat melaksanakan kehiduan demokrasi. Tulisan ini menunjukkan perubahan politik hukum pola berdemokrasi dari pemerintahan desa ke MPR menjadi dari MPR ke pemerintahan desa.Â DOI: https://doi.org/10.22304/pjih.v2n3.a10